Tracking control of robotic manipulator end-effector trajectory based on robust sliding mode method - Beibei Su (PLoS ONE, 2025)
This paper addresses the precise trajectory tracking of robotic manipulators (RMs) in automation tasks, particularly in hazardous environments. A dynamic model of the end-effector in Cartesian coordinates is developed to represent the system’s motion within the workspace. A robust sliding mode control (SMC) law is proposed to enhance control performance, with a focus on ensuring stability and accuracy in trajectory tracking. The SMC law is designed by deriving the relationship between control inputs and joint torques. Numerical simulations demonstrate that the proposed control method achieves high accuracy in trajectory tracking, with significant reductions in tracking errors. The results quantitatively show improved performance in both path following and system robustness, making the method suitable for real-time industrial applications.